A phase Ib trial of continuous once-daily oral afatinib plus sirolimus in patients with epidermal growth factor receptor mutation-positive non-small cell lung cancer and/or disease progression following prior erlotinib or gefitinib. (June 2017) - Moran, Teresa; Palmero, Ramón; Provencio, Mariano; Insa, Amelia; Majem, Margarita; Reguart, Noemí; Bosch-Barrera, Joaquim; Isla, Dolores; Costa, Enric Carcereny; Lee, Chooi; Puig, Marta; Kraemer, Sandrine; et al.
Highlights: Phase IB trial of afatinib plus sirolimus in patients with EGFR-TKI resistant NSCLC. The combination showed limited antitumor activity, similar to afatinib monotherapy. Data are insufficient to highlight a molecular pattern to predict treatment benefit. Overall, the combination of afatinib and sirolimus was poorly tolerated. Cumulative experience, including this study, precludes use of this combination. Abstract: Objectives: Dysregulation of the downstream PI3K/AKT/mTOR signaling pathway is a proposed mechanism of resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). We investigated safety and antitumor activity of afatinib plus sirolimus as a potential combination to reverse acquired resistance to EGFR-TKIs in a phase IB trial in patients with EGFR mutation-positive non-small-cell lung cancer ( EGFR mut NSCLC) and/or disease progression following prior erlotinib/gefitinib. Materials and methods: Patients with EGFR mut NSCLC and/or disease progression following at least prior erlotinib/gefitinib were included in the trial. The primary endpoint was incidence of dose-limiting toxicities (DLT) to determine the maximum tolerated dose (MTD). Four initial dose cohorts were proposed to evaluate DLTs. Other endpoints included tumor response, safety, progression-free survival (PFS) and pharmacokinetics. Results: Thirty-nine patients received afatinib and sirolimus. Additional dose cohorts were added since the second cohort (afatinib 40 mg/day and sirolimus 5 mg/day) was considered to have excessive toxicity. All patients experienced adverse events (AE) [grade 3: 66.7%; serious AE: 56.4%]. The most frequent AEs were diarrhea (94.9%), mucosal inflammation (64.1%), asthenia (53.8%) and rash (53.8%). Discontinuations and dose reduction due to AEs occurred in 23.1% and 25.6% of patients. MTD was determined as afatinib 30 mg and sirolimus 1 mg. Responses were observed in 5 patients (12.8%) [2 (5.1%) with confirmed partial response (PR); 3 (7.7%) with unconfirmed PR], and stable disease in 18 patients (46.2%). Four of the 5 responses were at doses above MTD. PFS at 6 months was estimated in 33.3% (median PFS 3.4 months). Pharmacokinetic parameters of afatinib and sirolimus were similar after single administration or in combination. Conclusion: The combination of afatinib and sirolimus showed lower responses than expected. Together with increased AEs and poor tolerability, this precludes clinical use and further clinical development of this combination. No pharmacokinetic interactions were observed. ClinicalTrials.gov Identifier: NCT00993499.